Designing a Sequence-Based Method for Identifying 14 High-Risk Carcinogenic HPV Types in Multiple Infections - Alimardani, Arezou; Dastmalchi, Narges; Rahimi, Hamzeh; Safaralizadeh, Reza (Infectious Disorders - Drug Targets, 2022)
Background: HPV tests have significant drawbacks in terms of detecting and differentiating types of the virus. PCR techniques provide timely and necessary results for patient care with high quality, sensitivity, and reasonable cost. Methods: The sensitivity of PCR depends on the primers. In this study, a method was designed that exploited PCR with designed primers (ScTd) by changing the annealing temperature (Ta) along with Sanger sequencing for pap smear samples. Sanger sequencing has confirmed that ScTd primers have a relative differentiation power using PCR. The primers caused a relative differentiation by PCR. In the pap smear sample 22 with contamination of types 16, 31, and 45, confirmed by dot blot hybridization, type 16 was not amplified at the specific Ta. Moreover, the band was observed at low Ta. Results: Sanger sequencing showed that type 16 was detected instead of type 52. Sequencing the heterozygous bands in multiple infections also led to the identification of different types. Moreover, with a combination of 7 pairs of primers, HPV types can be detected in multiple infections by PCR. Conclusion: As compared with the clinical dot blot hybridization technique, the utilization of complementary PCR and sequencing methods with designed primers can provide a higher positive predictive value in the detection of high-risk types.
Keywords: annealing temperature (Ta)